Evaluation of Imtasie Health Education Model Based on Kaili Culture to Improve Mother's Behavior in Exclusive Breasting - Jurana Tadjo; Jusuf Kristianto (Syntax Corporation Indonesia, 2023)
Evaluating the health education model on exclusive breastfeeding behavior as a basis for the success of the target of achieving exclusive breastfeeding through the implementation of a tested culture-based health education model. This research is quantitative. A total of 84 people who were divided into two groups, namely 42 people in the intervention group and 42 people in the control group were taken purposively according to the inclusion criteria. The intervention group received IMTASIE health education. Evaluate the health education model quantitatively with a quasi-experimental pre-test and post-test with a control group. Data was collected during the pre-test, intervention, and post-test. All data is collected by coaching nurses. The main research variables include myths, culture, knowledge, attitudes, practices and behavior of exclusive breastfeeding. The results of the quantitative study of the developed IMTASIE model had a significant effect on the practice of breastfeeding for 1 month with a p value of 0.001 (<0.05). There is a significant effect with a p value = 0.001 from the interventions carried out by nurses on increasing the practice of exclusive breastfeeding in the first 1 month of life. IMTASIE and its tools can be used in nursing care services individually or in groups and can be carried out in the community or at puskesmas in improving special group nursing care services and improving the quality of life of mothers and babies at an age prone to exclusive breastfeeding due to the influence of myths, culture and knowledge from family.